Assessing the level of community involvement in post-disaster housing reconstruction and current green design practices towards net-zero energy buildings - M, Sulzakimin; A., Adaji A.; A., Roy Hazli.; N. L., Mohammad Syabilee; O., Roshartini; M. R., Indera Syahrul; Z., Rozlin; I. Y., Ebenehi (2020)
The post-disaster housing reconstruction (PDHR) is a process discrete from the construction of housing when circumstances are undisturbed because sensitive measures are put in place following disasters occurrence. Most of the time, the successfulness of emergency relief efforts are usually recorded but the same cannot be said of PDHR projects because they often fail to meet sustainability factors. These days, the topic of sustainable building has become a leading concern in the academic, construction industries, and governmental agencies. Sustainability in the building sector has shifted emphasis towards a new concept called net-zero energy buildings (NZEBs). Data collection was done through a self-administration of structured questionnaires to 257 flood victims involved in the reconstruction projects. Findings indicated that community involvement in resource mobilisation and reconstruction process was insignificant due to misplacement of reconstruction priorities. This is capable of determining the failure of the project as beneficiaries’ requirements were not considered, and the construction industry is still unaware of NZEBs. This study is vital as stakeholders beginning with flood victims will have a more resilient housing, the government will be updated with robust strategies to solving resourcing and reconstruction issues, and donors will have value for their money.